THE EFFECT OF GEOGEBRA LEARNING MEDIA ON SPATIAL CAPABILITY AND UNDERSTANDING OF STUDENTS' MATHEMATICS LEARNING CONCEPTS - Nurul Hidayat; Zainal Abidin; Yayan Eryk Setiawan (USN Kolaka, 2024)
The purpose of this study was to see how geogebra learning media on flat sided geometrical material affected the spatial abilities and understanding of learning ideas in Probolinggo Private MTs class 8 pupils. The experimental research approach was given to courses VIII. The control class is VIII-B with 30 students and the experimental class is VIII-C with 25 students. Quasi experiment design in this research are used. Pre and Post-tests were used to examine the influence of geogebra on students' knowledge of learning concepts, while surveys were used to determine the effect of geogebra on students' psychological capacities. The data was analyzed using the Anova test. The findings of the study reveal that: (1) Geogebra learning media on flat sided geometric material influence students' spatial ability. (2) Students' knowledge of learning ideas is improved when Geogebra learning media are used in class functional content compared to students who do not use Geogebra.